P2x7 Receptor Signaling Blockade Reduces Lung Inflammation and Necrosis During Severe Experimental Tuberculosis - Santiago-Carvalho, Igor; Almeida-Santos, Gislane de; Bomfim, Caio César Barbosa; Souza, Paula Carolina de; Silva, Juan Carlo Santos e; Melo, Bruno Marcel Silva de; Amaral, Eduardo Pinheiro; Cione, Marcos Vinícios Pinheiro; Lasunskaia, Elena; Hirata, Mario Hiroyuki; Alves-Filho, José Carlos Farias; Nakaya, Helder Imoto; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The risk of developing severe forms of tuberculosis has increased by the acquired immunodeficiency syndrome (AIDS) epidemic, lack of effective drugs to eliminate latent infection and the emergence of drug-resistant mycobacterial strains. Excessive inflammatory response and tissue damage associated with severe tuberculosis contribute to poor outcome of the disease. Our previous studies using mice deficient in the ATP-gated ionotropic P2X7 receptor suggested this molecule as a promising target for host-directed therapy in severe pulmonary tuberculosis. In this study, we assessed the effects of P2X7 pharmacological blockade on disease severity. First, we observed an increase in P2RX7 gene expression in the peripheral blood of tuberculosis patients compared to healthy donors. Lung leukocytes of mice infected with hypervirulent mycobacteria also showed increased expression of the P2X7 receptor. P2X7 blockade in mice with advanced tuberculosis recapitulated in many aspects the disease in P2X7-deficient mice. P2X7-directed therapy reduced body weight loss and the development of inflammatory and necrotic lung lesions, as well as delayed mycobacterial growth. Lower TNF-α production by lung cells and a substantial reduction in the lung GR-1+ myeloid cell population were observed after P2X7 inhibition. The effector CD4+ T cell population also decreased, but IFN-γ production by lung cells increased. The presence of a large population with characteristics of myeloid dendritic cells, as well as the increase in IL-6 production by lung cells, also indicate a qualitative improvement in the pulmonary immune response due to P2X7 inhibition. These findings support the use of drugs that target the P2X7 receptor as a therapeutic strategy to improve the outcome of pulmonary tuberculosis.